2003
DOI: 10.1038/sj.cdd.4401150
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Fas-mediated apoptosis by attenuated production of mitochondria-derived reactive oxygen species

Abstract: The role of reactive oxygen species (ROS) production in death receptor-mediated apoptosis is ill-defined. Here, we show that ROS levels play a role in moderating Fas-dependent apoptosis. Treatment of Jurkat T cells with oligomycin (ATP-synthase inhibitor) or (mitochondrial uncoupler) and Fas-activating antibody (CH11) facilitated rapid cell death that was not associated with decreased ATP production or increased DEVDase activity and cytochrome c release. However, a decrease in cellular ROS production was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 37 publications
5
43
2
Order By: Relevance
“…Our observation that NAC, MnTBAP, and C 60 (D3) did not interfere with CH11-triggered apoptosis (Figure 7) may seem contradict with the report that decreased cellular ROS production by oligomycin or FCCP enhances Fasinduced apoptosis (Aronis et al, 2003). We speculate that a reason for such discrepancy is the concentrationdependent physiological effect for ROS.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Our observation that NAC, MnTBAP, and C 60 (D3) did not interfere with CH11-triggered apoptosis (Figure 7) may seem contradict with the report that decreased cellular ROS production by oligomycin or FCCP enhances Fasinduced apoptosis (Aronis et al, 2003). We speculate that a reason for such discrepancy is the concentrationdependent physiological effect for ROS.…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, the antioxidants used in the present study, effective in reducing stress stimulitriggered ROS burst (Alleva et al, 2001), are likely not as effective as oligomycin and FCCP in the abrogation of basal ROS production. Together, the observations that CH11-induced death is not affected by conventional antioxidants (Hug et al, 1994;Schulze-Osthoff et al, 1994;Alleva et al, 2001) and is augmented by oligomycin and FCCP (Aronis et al, 2003), suggest that intracellular basal ROS production, but not Fastriggered ROS increase, is participated in the apoptotic processes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although the redox state of a cell is considered to be an important determinant of its susceptibility to various apoptotic stimuli, the mechanism by which the redox state contributes to death receptor-mediated apoptosis remains unclear. Numerous reports have revealed a role for ROS as mediators of the death program, but other reports have shown that oxidative stress inhibits apoptotic signaling 13,[23][24][25] In this study, we have demonstrated that suppression of TRAIL-induced ROS levels sensitizes cells to TRAILmediated apoptosis in a caspase-dependent manner, and that this effect occurs before changes in TRAIL-induced apoptosis can be detected. These results imply that ROS can act as anti-apoptotic mediators in TRAIL-mediated signal transduction and can render tumor cells resistant to TRAIL-induced apoptosis, depending on the cellular context.…”
Section: Discussionmentioning
confidence: 50%